Immune surveillance and humoral immune responses in kidney transplantation – A look back at T follicular helper cells - Subburayalu, Julien (Frontiers in Immunology, 2023)
T follicular helper cells comprise a specialized, heterogeneous subset of immune-competent T helper cells capable of influencing B cell responses in lymphoid tissues. In physiology, because of viral infection or vaccination, this interaction chiefly results in the production of protecting antibodies and humoral memory. In the context of transplantation, immune surveillance provided by T follicular helper cells can take a life of its own despite matching of human leukocyte antigens and employing the latest immunosuppressive regiments. This puts kidney transplant recipients at risk of subclinical and clinical rejection episodes with a potential risk for allograft loss. In this review, the current understanding of immune surveillance provided by T follicular helper cells is described in the context of physiology, viral infection, and solid organ transplantation. Sensitization of T follicular helper cells with the subsequent emergence of detectable donor-specific human leukocyte antigen antibodies, non-human leukocyte antigen antibodies against autoantigens and implications for kidney transplantation and lessons learnt from other transplantation setting with special attention to antibody-mediated rejection will be addressed.